Impact of Green Human Resource Management Practices on Perceived Environmental Sustainability: Employee Perspectives from Nepalese Commercial Banks - Hakuduwal, Kishor; KC, Suraj (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study aims to analyze the perception of employees working in commercial banks regarding green human resource management (GHRM) practices and environmental sustainability in Nepalese commercial banks. The research specifically focuses on five components of GHRM: green recruitment and selection, green training and development, green reward and compensation, green performance management, and green employee involvement. Methods: A structured questionnaire was used to collect primary data from 397 respondents through an opinion survey conducted in the Kathmandu Valley. Convenience sampling was employed to select participants from commercial banks. The study adopted a descriptive and explanatory research design. Statistical tools such as mean, correlation, and regression analysis were used to analyze the collected data. Results: The analysis revealed that all five components of green human resource management practices, green recruitment and selection, green training and development, green reward and compensation, green performance management, and green employee involvement, have a significant impact on the perceived environmental sustainability of Nepalese commercial banks. Furthermore, employees demonstrated awareness of GHRM practices and recognized their importance in achieving environmental sustainability. Conclusion: The study highlights the vital role of GHRM practices in enhancing environmental sustainability within commercial banks in Nepal. The findings can assist Nepalese commercial banks in formulating effective policies and programs that incorporate green HRM as a strategic tool for promoting organizational sustainability.